On-line store image: identification of measurements and measuring scales - Correia, Rafaela Rodrigues; Tezza, Rafael; Cancellier, Éverton Luís Pellizzaro de Lorenzi (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
An on-line store image assists in satisfying consumer needs and, despite its importance, it is still a concept under construction. In this context, this study aims to identify the different ways of measuring on-line store images, showing how the scales were created, adapted and replicated compiling this knowledge that is dispersed. For this purpose, a bibliographical compilation of articles was made that address the ways of measuring the image of an on-line store from 2003 to 2015. The results point to a diversity of conceptual frameworks and dimensions. The most recurrent dimensions were: atmosphere of the on-line store, pleasure in buying and ease of use. Dimensions such as brand image, price, promotion, reputation and connection with other channels were little used by researchers, appearing only in more recent studies. It has been found that there is no universally accepted scale for measuring the image of the on-line store.